THE EFFICIENCY OF ISLAMIC AND CONVENTIONAL BANKS IN PAKISTAN (Malaysian Management Journal, 2020)
In Pakistan, the conventional banks start their functions after the independence of Pakistan and followed by the introduction of the Islamic banking’s. In this study, four Conventional and four Islamic banks were selected. The different types of ratios will be used to check the performance of banking sector these ratios are profitability, liquidity, investment and solvency ratios. The different types of ratios were used to check the performance of banking sector and to evaluate the trends of Islamic and commercial banks. The objectives of our study were to evaluate the trend of performance of conventional and Islamic banks and analyses the key performance indicators of the banking systems. The SPSS version 20 was used and the t-test was applied to the data. The findings revealed that the conventional banks were more efficient than the Islamic banks.